2006
DOI: 10.21236/ada456310
|View full text |Cite
|
Sign up to set email alerts
|

IBM's Statistical Question Answering System - TREC-11

Abstract: In this paper, we document our efforts to extend our statistical question answering system for TREC-11. We incorporated a web search feature, and novel extensions of statistical machine translation as well as extracting lexical patterns for exact answers from a supervised corpus. Without modification to our base set of thirty-one categories, we were able to achieve a confidence weighted score of 0.455 and an accuracy of 29%. We improved our model on selecting exact answers by insisting on exact answers in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 4 publications
0
105
0
2
Order By: Relevance
“…Many techniques have been investigated in this area. The most successful techniques were the ones based on density [17], [20], [3](JIRS is based on density, see Figure 2 and the JIRS architecture description below) and the ones based on terms overlap [4], [9]. However, there are other works which investigated the efficiency of the PR module when the the order of the question terms is respected [2] and the possibility of using semantic information to obtain the relevant passages [16].…”
Section: The Arabic-jirs Passage Retrieval Systemmentioning
confidence: 99%
“…Many techniques have been investigated in this area. The most successful techniques were the ones based on density [17], [20], [3](JIRS is based on density, see Figure 2 and the JIRS architecture description below) and the ones based on terms overlap [4], [9]. However, there are other works which investigated the efficiency of the PR module when the the order of the question terms is respected [2] and the possibility of using semantic information to obtain the relevant passages [16].…”
Section: The Arabic-jirs Passage Retrieval Systemmentioning
confidence: 99%
“…Although question classification plays a vital role in most QA systems, many factors influence the overall ability of a system to produce the correct answer to a given question. It has been shown that parallel improvements in question classification accuracy, retrieval of candidate answer, named entity tagging, and answer extraction are needed to improve the overall performance of a QA system [12].…”
Section: Overviewmentioning
confidence: 99%
“…Since it is not possible to list all such systems, we briefly describe several. Among these are IBM's TREC-9 system [12] that utilizes maximum entropy models [7]. It uses a mix of syntactic and semantic features (see Section 5).…”
Section: Related Workmentioning
confidence: 99%
“…Rule 1: Question word in a chunk of length more than one (see Example (1) in Table 2). Qp = question word + headword in the same chunk…”
Section: Question Pattern Extractionmentioning
confidence: 99%
“…An automated question answering (QA) system receives a user's natural-language question and returns exact answers by analyzing the question and consulting a large text collection [1,2]. As Moldovan et al [3] pointed out, over 60% of the QA errors can be attributed to ineffective question processing, including query formulation and query expansion.…”
Section: Introductionmentioning
confidence: 99%